AI is Changing the World: For Better or for Worse? - Grewal, Dhruv; Guha, Abhijit; Becker, Marc (Journal of macromarketing, 2024)
The profound impacts of artificial intelligence (AI) will continue to evolve over the next several decades, and many of these impacts will emerge through marketing-related AI applications. Therefore, marketers, public policymakers, firms, researchers, and individual consumers must recognize and understand the benefits that AI offers, as well as the perils that it presents, both now and in the future. A literature review surfaced three themes – that AI will augment and (potentially) replace human intelligence, that AI will evolve into an empathetic and trusted companion, and that AI will create novel tensions. Next, this article outlines three stages of AI development, from an early stage with much promise, to a stage with many benefits, to a stage wherein AI-related tensions emerge. Finally, this article outlines three grand challenges: (1) preserving and growing human capability, (2) protecting societal belonging and human connection, and (3) ensuring equitable sharing of AI benefits. Addressing such challenges, along with related concerns (e.g., privacy, ethics), can enable society to reap the benefits of AI fruitfully and in an equitable manner that truly improves the quality of life.